A Portrait of Judge P. H. Kooijmans – A Passionate Advocate of the Rule of Law in International Affairs. (6th November 2014) - SCHRIJVER, NICO
Abstract In 2013 the Netherlands lost its standard bearer in international law. After a short period of illness, Pieter Hendrik Kooijmans died at the age of 79 on 13 February 2013. Some time before his illness the author had an extensive and frank interview with Judge Kooijmans who reflected on his life and work, especially on his intellectual formation, his understanding of the essence and core functions of law, his experiences as UN special rapporteur on torture, his ideas on reform of the International Court of Justice, and the great changes that have taken place in international law. This portrait shows a fine man with a strong sense of justice who was fully dedicated to the substance of public international law without turning a blind eye to its shortcomings and relative influence in international and domestic affairs. The interview is preceded by an introduction and concludes with some observations on his long and productive life in the service of peace, justice, and respect for human rights through the law.